The Effect of Acidic Beverages on Hardness of Two Different Composite Filling Materials - Ashar Hussain, Aisha Mehboob, Areeba Laghari, Mowaffaq Abdullmomen Al Absi, Hafiz Mahmood Azam, Muhammad Siddique Qazi (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Acidic beverages are widely consumed, and their erosive effects on dental materials have become a significant concern. Composite resin materials used in dental restorations are particularly vulnerable to acidic exposure, potentially leading to a reduction in their surface hardness. Objective: This study aimed to evaluate the effect of acidic beverages, specifically Pepsi cola and orange juice, on the hardness of two types of composite filling materials: micro-filled and nano-hybrid composites. Study setting and duration: This observational comparative cross sectional study was conducted in the department of Dental Materials at Isra Dental College, Isra University and Department of Metallurgy & Materials Engineering at Mehran University of Engineering & Technology, Jamshoro. This study was completed in six (06) months (from September 2022 to February 2023). Methods: A total of 20 specimens, including micro-filled composite (Master Fill, Biodinamica) and nano-hybrid composite (CharmFilplus, DentKist), were prepared. Each composite type consisted of 10 samples. Specimens were immersed in Pepsi cola (pH 2.60) and Nestle orange juice (pH 3.94) for 30 minutes. Vickers micro-hardness was measured before and after immersion, applying a load of 1 kg for 15 seconds on each sample. The mean hardness values and their differences were analyzed using paired t-tests, with a significance level of 0.05. Results: Both composite types showed significant reductions in hardness after immersion in acidic beverages. For micro-filled composites, the mean hardness decreased from 57.18 ± 0.48 VHN to 48.42 ± 0.74 VHN in Pepsi cola (mean difference = 8.76, p < 0.05) and from 57.02 ± 1.22 VHN to 52.04 ± 1.29 VHN in orange juice (mean difference = 4.98, p < 0.05). Nano-hybrid composites showed a hardness reduction from 63.38 ± 1.87 VHN to 54.20 ± 1.10 VHN in Pepsi cola (mean difference = 9.18, p < 0.05) and from 63.48 ± 3.19 VHN to 59.40 ± 1.33 VHN in orange juice (mean difference = 4.08, p < 0.05). Comparison between composites showed nano-hybrid composites exhibited greater hardness than micro-filled composites in both acidic media. Conclusion: Acidic beverages such as Pepsi cola and orange juice significantly reduce the hardness of both micro-filled and nano-hybrid composite materials. Nano-hybrid composites retained a higher hardness level than micro-filled composites under acidic conditions, suggesting they may be more suitable for dental restorations exposed to acidic environments. Further research could explore alternative materials with improved resistance to acidic erosion for enhanced dental restoration durability. Keywords: Composite Resins, Acidic Beverages, Tooth Erosion, Dental Materials, Microhardness.